Uncovering the determinants of health in deprived urban neighborhoods in Accra, Ghana: a qualitative and participatory reconnaissance study - Amedzro, Nina; Anaseba, Dominic; Darkwa, Akosua Gyasi; Twumasi, Afua; Ayim, Andrews; Ansah-Ofei, Adelaide Maria; Dovlo, Delanyo; Awoonor-Williams, John K.; Agongo, Erasmus Emmanuel Akurugu; Agyepong, Irene Akua; Elsey, Helen (Frontiers in Public Health, 2024)
Background: Delivering primary care services within the context of rapid urbanisation and a changing disease burden is a major challenge in sub-Saharan Africa. Rural models of primary care, including the "Community-based Health Planning and Services" (CHPS) programme in Ghana, have shown improved health outcomes. However, adapting these to the urban context has proved problematic. Differences in the determinants of health found in these settings may help to explain the challenges of delivering CHPS in poor urban neighbourhoods in Accra. To inform the redesign of CHPS for the urban context, we aimed to understand the determinants driving health and engagement with health services in three informal settlements in Accra.Methods: This study formed a reconnaissance phase for a subsequent participatory action research study. We used qualitative and participatory methods to explore the influence of wider and proximal determinants on health and the use and perceptions of CHPS. Three transect walks with community leaders across the study settings informed interview guides and the recruitment of suitable participants for key informant and focus group interviews. Using a Framework Approach, we analysed transcripts and reports from these activities and developed themes and sub-themes in participants' experiences accessing healthcare.Results: Our findings highlight the importance of wider and proximal determinants of health including physical environment, gender and other social stratifiers including age, ethnicity, religion and disability, on health, health seeking behaviour and personal behaviours such as substance misuse, tobacco use and alcohol. Utilisation of CHPS was low and seen primarily as a service for maternal and child health. Private providers, ranging from informal drug stores to private clinics, were used most commonly. Community leaders and groups were active, but engagement was limited by opportunity costs for members.Conclusions: Traditional service delivery packages need to be adapted to include non-communicable diseases driven by risk behaviours such as tobacco, unhealthy diet, alcohol and substance abuse. Assets such as volunteerism and nurses embedded within communities are challenging to attain in complex urban settings, yet other assets exist including occupational associations and a range of informal and private providers that could support delivery of preventive and promotive health care with equitable reach.